A long way from home - Baguley, Elizabeth; Chapman, Jane (London : Little Tiger Press, 2008)
Noah Rabbit, having asked his friend the albatross to take him away from the cramped quarters of his burrow, begins to miss his family and the safety of his home.
2.5
K-3
Keywords: Albatros -- Juvenile fiction; Rabbits -- Juvenile fiction; Albatros -- Fiction; Rabbits -- Fiction